Architects between Paternalism and Client-Orientation: Professional Ethics, Financial Criteria and Users in Contemporary Capitalist Economies - Ötsch, Silke (Momentum Quarterly, 2013)
The paper deals with the effects of financial pressure on the professional ethos using architects as a case in point. Based on data from comparative qualitative case studies in four different capitalist economies (Austria, United Kingdom, France, USA), I will show that beyond the traditional ‘paternalistic’ ethos a number of architects demonstrate a ‘client-oriented’ entrepreneurial ethos. I question common interpretations of ‘client-orientation’ as a sign of the democratization of architecture. Democratization cannot be put into practice within the boundaries of the profession, but must be implemented by including the economic and societal framework.